2022
DOI: 10.37689/acta-ape/2022ao02912
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome congênita pelo vírus zika: análise das redes de apoio de pais

Abstract: Síndrome congênita pelo vírus zika: análise das redes de apoio de paisCongenital zika syndrome: analysis of parent support networks Síndrome congénito por el virus del zika: análisis de las redes de apoyo de padres

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
(27 reference statements)
0
3
0
3
Order By: Relevance
“…A study on the support network of caregiver mothers found their dissatisfaction with the care service closest to their home, which led them to seek care in a specialized service, despite the fact that this causes inconvenience, due to the greater distance to be covered to the aforementioned specialized service (22) . Among the reasons that motivate families to seek these services, the following stand out: parents' trust in the health professionals who work there, expectations about the quality of care provided, personal and/or social network experience and satisfaction with the service (22,23) . Therefore, it is inferred that it is necessary to expand strategies beyond public policy makers, in order to involve educational institutions in the training of professionals committed to strengthening PHC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on the support network of caregiver mothers found their dissatisfaction with the care service closest to their home, which led them to seek care in a specialized service, despite the fact that this causes inconvenience, due to the greater distance to be covered to the aforementioned specialized service (22) . Among the reasons that motivate families to seek these services, the following stand out: parents' trust in the health professionals who work there, expectations about the quality of care provided, personal and/or social network experience and satisfaction with the service (22,23) . Therefore, it is inferred that it is necessary to expand strategies beyond public policy makers, in order to involve educational institutions in the training of professionals committed to strengthening PHC.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, childcare, early stimulation actions, referral to specialized assistance and identification of families at social risk are strategic care actions for children with CZS and their families, which can be developed by PHC professionals (22) . The professionals in the referred study also mentioned integration/communication between the different points of the network as a potential aspect in the care of children with the syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo sobre a rede de suporte de mães cuidadoras, constatou a insatisfação delas com o serviço/atendimento mais próximo à sua residência, o que as levam a procurar atendimento em um serviço especializado, apesar de isto exigir esforços relacionados com o deslocamento devido a distância maior (22) . Dentre as razões que motivam as famílias em busca desses serviços, destacam-se a confiança dos pais nos profissionais de saúde que lá atuam, as expectativas sobre qualidade do cuidado prestado, a experiência pessoal e/ou da rede social e a satisfação com o atendimento (22,23) . Logo, infere-se que é preciso expandir as estratégias para além dos formuladores de políticas públicas, de modo a envolver instituições de ensino na formação de profissionais comprometidos com o fortalecimento da APS.…”
Section: Discussionunclassified
“…Neste sentido, a puericultura, as ações de estimulação precoce, o encaminhamento à assistência especializada e a identificação das famílias com risco social, constituem ações estratégicas de cuidado às crianças com SCZ e suas famílias, que podem ser desenvolvidas pelos profissionais da APS (22) . Os profissionais deste estudo também apontaram a integração/comunicação entre os diferentes pontos da rede, como aspecto potencial no cuidado à criança com a síndrome.…”
Section: Discussionunclassified